Taxonomic Revision of the South American Genus Eudius and First Insights into the Phylogeny of the Tribe Eudiagogini (Curculionidae: Entiminae) - Rincón, Judy A. (2025)
The genus Eudius Schoenherr is classified in the broad-nosed weevil tribe Eudiagogini (Entiminae) and harbors two species, Eudius quadrisignatus Gyllenhal and Eudius jocosus Fahraeus, which are only known from their original descriptions. It is endemic to the Brazilian Atlantic Forest, which is one of the most threatened biomes in the world despite being a biodiversity hotspot. In this contribution, and as part of a wider systematic and phylogenetic study on tribe Eudiagogini, we performed a taxonomic revision of the genus Eudius and made preliminary phylogenetic analyses of Eudiagogini based on morphology and molecular evidence. Specimens from seven collections in Argentina, Brazil, and Europe were examined. Diagnosis and redescription of the genus and its species are provided, along with photographs of habits, and illustrations of diagnostic characters and new geographic distribution data. Additionally, a lectotype is designated for each species. The morphology-based phylogenetic analysis was performed under maximum parsimony, using 60 characters from adults coded for representative species from eight genera of Eudiagogini and other related tribes of Entiminae. As a result, monophyly of the genus Eudius and its placement within the tribe Eudiagogini are confirmed, while placement of the genus Chileudius Kuschel in Eudiagogini is refuted. A first molecular phylogenetic analysis of the tribe was also designed, using DNA sequences (of the COI barcode and two ribosomal markers) available for some representatives of Eudiagogini and outgroup taxa, analyzed under parsimony and maximum likelihood. The molecular results are consistent with morphology in recovering a monophyletic tribe Eudiagogini, excluding the genus Chileudius, which is now placed as incertae sedis in Entiminae, pending further analyses. Informative characters within the tribe are discussed, with Eudius supported as a clade by the basally connate tarsal claws and by the sclerites present in the bursa of female genitalia. Synapomorphies justifying the revised concept of Eudiagogini as a natural tribe are highlighted, like the presence of a cavernous prementum and the metaventrite with a spine-like swelling anterior to each metacoxa.